Preparing the High School Classroom for Migrant English Language Learners - Megan Elizabeth Rouse (Profile: Issues in Teachers' Professional Development)
In United States schools, the rate of immigrant English language learners is rapidly rising, affecting the lives of both students and teachers. This article will discuss the best ways to facilitate the students’ language learning in a school setting; the type of structure, goals, and standards that can be expected; as well as ways to change the preconceived notions of teachers. The implications of this work are significant. We are obligated to support our English language learners with up-to-date teaching approaches and modifications to harness their strengths and enable them to succeed as learners in an English-speaking setting.